2D underwater acoustic metamaterials incorporating a combination of particle-filled polyurethane and spiral-based local resonance mechanisms. (15th July 2019) - Zhong, Haibin; Gu, Yinghong; Bao, Bin; Wang, Quan; Wu, Jiuhui
Abstract: This paper develops an underwater acoustic metamaterial plate with potential advantages of low-frequency broadband sound absorption and high hydrostatic pressure resistance. In this research, a new acoustic metamaterial embedding particle-filled polyurethane (PU) and spiral-based local resonance mechanism for underwater sound absorption is investigated numerically and experimentally. Specifically, the proposed metamaterial is composed of particle-filled PU damping materials and a square lattice of spiral resonators. The thickness of the proposed plate structure occupying most of the area is thin and equals to 4 mm. Wave propagation properties of the proposed metamaterial are obtained by using the finite element (FE) method. Compared to the underwater sound absorption coefficient, the formation mechanisms of the locally resonant band gaps are investigated based on the modal analysis of plate modes and local resonances. Results show that the location and bandwidth of newly generated locally low-frequency resonant band gaps are greatly affected by the interaction between particle-filled PU and the spiral resonator within every periodic cell. In addition, the theoretical results of the underwater sound absorption coefficient of the proposed metamaterial are compared with the experimental results. In the frequency domain [0.8 kHz, 6 kHz], the average sound absorption coefficient of the proposed metamaterial plate under normal atmospheric pressure is 0.54. Furthermore, the sound absorption coefficient of the proposed structure is experimentally studied under different hydrostatic pressure conditions. Specifically, the proposed metamaterial structure achieves average sound absorption coefficient of 0.51 in the frequency range [1.5 kHz, 6kHz] under 0.5 MPa.